Nursing Care for Memory Disorders In Patient A with Alzheimer's Type Dementia At Iryou Houlin Aiwa Kai Ikeda En Japan - Atika Wulandari; Mariah Ulfah; Madyo Maryoto (CV. AFDIFAL MAJU BERKAH, 2026)
Alzheimer's dementia is a global health problem with increasing prevalence along with the aging population, characterized by memory impairment that interferes with independence. This study aims to describe nursing care for memory impairment in Patient A through the nursing process. The type of qualitative descriptive case study was conducted at Iryou Houlin Aiwa Kai Ikeda En Japan, September 2025. The population of elderly with Alzheimer's dementia (91 patients), a purposive sample of one patient (Mrs. A, MMSE 19). Instruments include MMSE-J, assessment sheets, reminiscence media; source triangulation analysis and case-theory. The results showed that the diagnosis of memory impairment and risk of injury were partially resolved after 3x24 hours of reminiscence therapy (MMSE score increased 19→20), long-term memory improved but short-term memory was limited, and the risk of falls was controlled. It was concluded that reminiscence therapy is effective in maintaining the cognitive function of the elderly in a supportive manner.